Analisa Perancangan Desain Aplikasi Pengelolaan Absensi dan Sistem Penggajian Karyawan pada Daihatsu Capella Medan Cabang Padang - Tito; Redha Ramadhani; Annisak Izzaty Jamhur (Universitas Putra Indonesia YPTK Padang, 2020)
The payroll system is one of the things related to the management of the welfare of the workforce so it must be given special attention by the company in order to achieve its objectives. Salary has a very important meaning for employees because salary is a reflection of the value of the work, and also as an encouragement in a job of their performance, both for the company, the community, and for themselves. In the form of a company's payroll system, employee absence is very influential in taking employee salaries. As in the field research, it can be taken from Daihatsu Capella Medan, Padang Branch. This PT is a company that already exists in several regions in Indonesia